Investigating the Role of OCB and Intellectual Capital on Job Performance through Knowledge Sharing Behavior - Sudarsih,; Supriyadi,; Putri , Nadia Azalia (International Journal of Psychosocial Rehabilitation, 2020)
This paper provides new insights by testing the effect of OCB and intellectual capital on knowledge sharing behavior and job performance. As many as 172 employees of Representative Office of Bank Indonesia in East Java, Indonesia, were involved.The data was analyzed using path analysis. The results revealed that: a) OCB has a significant direct positive effect on knowledge sharing behavior; b) Intellectual capital has a significant direct positive effect on knowledge sharing behavior, c) OCB has a significant direct positive effect on job performance; d) intellectual capital has a significant direct positive effect on job performance; e) knowledge sharing behavior has a significant direct positive effect on job performance; f) knowledge sharing behavior mediates the indirect effect of OCB on job performance, and i) knowledge sharing behavior mediates the indirect effect of intellectual capital on job performance. These results provide new insight for organization in improving their employees’ job performance and knowledge sharing behavior in this competitive and disruptive era.